Five-factor model of personality disorder: a proposal for DSM-V - Widiger, Thomas A; Mullins-Sweatt, Stephanie N (Annual review of clinical psychology, 2009)
The predominant dimensional model of general personality structure within psychology is the five-factor model (FFM). Research indicates that the personality disorders of the American Psychiatric Association's diagnostic manual can be understood as maladaptive variants of the domains and facets of the FFM. The current review provides a proposal for the classification of personality disorder from the perspective of the FFM. Discussed as well are implications and issues associated with an FFM of personality disorder, including the integration of a psychiatric nomenclature with general personality structure, the inclusion of a domain of openness to experience, the identification of problems in living associated with maladaptive personality traits, the setting of a diagnostic threshold, prototypal matching, feasibility, and clinical utility.